Digital Marketing Communication Strategy For Strengthening Bengkulu City Tourism Brand - Ayuh, Eceh Trisna; Darmi, Titi; Ekowati, Sri; Adhrianti, Lisa; Hafizah, Evi (Universitas Muhammadiyah Ponorogo, 2022)
Bengkulu City has various historical, cultural and natural tourism assets, this has allowed Bengkulu City to become a tourism city. The internet penetration rate of Indonesia's population continues to increase from year to year. However, the regional government of Bengkulu City has not read the opportunities for digital marketing platforms and made branding efforts for the Bengkulu tourism sector. This study aims to determine the digital marketing branding communication strategy for Bengkulu city tourism destinations. The research approach used is a qualitative approach based on the philosophy of postpositivism. This research is a case study research using the concept of AISAS theory which consists of Attention, Interest, Search, Action and share. The results of this study state that digital marketing communications carried out by the Bengkulu government focus on creating marketing content to create tourist attraction through social media. Image quality, content content, content duration and words in the content are important parts that must be considered. In addition, it is known that the creation of digital marketing content requires quite a lot of effort so that the content is of high quality and attractive, it is necessary to have human resources with special digital skills and a qualified team of creators.